Semimetal 1H‐SnS2 Enables High‐Efficiency Electroreduction of CO2 to CO. Issue 10 (1st September 2020) - Xu, Jie; Lai, Shuhua; Hu, Min; Ge, Shangmeng; Xie, Ruicong; Li, Fan; Hua, Dandan; Xu, Heng; Zhou, Huang; Wu, Rui; Fu, Jiantao; Qiu, Yuan; et al.
Abstract: Controlling the selectivity of products in CO2 fixation is essential to obtain desired products using phase engineering. In this study, stable semimetal 1H‐SnS2 nanosheets are successfully synthesized by hydrogen‐assisted low‐temperature calcination for the first time. Compared with semiconductor 1T‐SnS2, the 1H‐SnS2 exhibits ultrahigh CO selectivity with a Faradaic efficiency of 98.2% at −0.8 V (vs reversible hydrogen electrode) and a partial current density of 10.9 mA cm −2 in the electrocatalytic CO2 reduction reaction. Theoretical calculations indicate that the *COOH intermediate is more stable on 1H‐SnS2 surface than 1T‐SnS2 surface and thus promotes the CO production. This work shows that phase engineering control can be an effective approach to regulate the selectivity of products in CO2 RR of transition metal dichalcogenides. Abstract : Metastable 1H‐SnS2 is first applied as an efficient electrocatalyst for CO2 fixation with a high CO Faradaic efficiency of 98.2% and a current density of 12.0 mA cm −2 . Theoretical calculations reveal that 1H‐SnS2 is more likely to facilitate the formation of *COOH. This work suggests that phase transition engineering is promising to regulate the products selectivity of CO2 electroreduction.